Downregulation of miR‐21 is Involved in Direct Actions of Ursolic Acid on the Heart: Implications for Cardiac Fibrosis and Hypertrophy. Issue 4 (7th July 2015) - Dong, Xingli; Liu, Shangkun; Zhang, Lingling; Yu, Siming; Huo, Linman; Qile, Muge; Liu, Lu; Yang, Baofeng; Yu, Jinling
Summary Purpose Myocardial fibrosis contributes to cardiac remodeling and loss of cardiac function in myocardial infarction and heart failure. This study used in vitro and in vivo models to examine the effects of ursolic acid (UA) on myocardial fibrosis and to explore its potential mechanism. Methods Transverse aortic constriction (TAC) surgery was performed in mice to induce cardiac hypertrophy and fibrosis. UA was orally administered 1 week prior to TAC. Two weeks after TAC, myocardial pathology was detected using Masson's trichrome staining and transmission electron microscopy, and heart‐to‐body weight ratio was measured. For in vitro studies, cultured cardiac fibroblasts were treated with serum in the presence or absence of UA. The relative levels of miR‐21 and p‐ERK/ERK, collagen content and cell viability were measured. Results Ursolic acid attenuated pathological cardiac hypertrophy and myocardial fibrosis in vivo induced by TAC. Downregulation of miR‐21 and p‐ERK/ERK were observed in myocardial fibroblasts treated with UA in a dose‐dependent manner compared with the control group both in vitro and in vivo. Conclusions Our study demonstrates that UA can inhibit myocardial fibrosis both in vitro and in vivo, and the effects of UA on myocardial fibrosis may be due to the inhibition of miR‐21/ERK signaling pathways.